Hollow Triangular Cross-Section Calculating Precast-Monolithic Beams Methods with Account for Concrete Nonlinear Properties - Azizov, Taliat; Kochkarev, Dmitriy; Galinska, Tatyana; Jurkowska, Nadzieja (International Journal of Engineering and Technology, 2018)
The article examines precast-monolithic reinforced concrete beams with a cross section in the form of a hollow triangle. The advantages of such beams are presented and say that their stiffness in torsion is ten times bigger than the similar rigidity of a T-beam with the same stiffness and bending resistance. The article introduces the method of manufacturing such beams without the use of form work which was developed by the author of the article. Earlier the authors investigated the stiffness of such beams in torsion and it is mentioned in the article. However, stiffness and bending resistance are not investigated. Resistance and stiffness of precast-monolithic beams under bending differs from the resistance and stiffness of the monolithic ones. Consequently, taking into account the nonlinear properties of materials the calculation of such beams is different. The method for calculating beams under bending is introduced and it is based on the application of the flat section hypothesis. This method is used in conventional methods of calculation. The difference from the traditional calculation is the addition of equilibrium stress to the equations which are perceived by sections of monolithic concrete with physical and mechanical characteristics that differ from those of the main part of the structure. In calculation the cross-section of the beam is reduced to the equivalent T-section. The obliquity of the side faces is taken into account and the thickness of the edge of the equivalent T-beam is understood as the doubled thickness of the side edge divided by the sine of the angle of obliquity of the edges. In order to apply this calculation method, at first, it is necessary to check the sufficiency of the presence of a transverse reinforcement in the grid which is laid in the construction of the structure. With a sufficient diameter and rod spacing of transverse reinforcement which are calculated according to the authorsâ€™ previously developed method, the structure can be calculated as monolithic with sections with different material characteristics according to the method introduced in the article. The calculations based on the above procedure showed a good match with the results of experimental studies of the authors.Â Â